2015
DOI: 10.1177/0040517515578328
|View full text |Cite
|
Sign up to set email alerts
|

Exploring geometric morphology in shape memory textiles: design of dynamic light filters

Abstract: Thermo-responsive Shape Memory Alloys are able to adopt a temporary configuration and return to their programmed shape when heated to a determined activation temperature. The possibility to integrate them in textile substrates creates potential to develop smart textiles whose shape change explores functional and expressive purposes. The aim of this research is to develop shape memory woven textiles in which dynamic behavior achieves predefined geometric shapes. The requirement of geometric morphology was addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This enables complex faceted or curved geometries from folding a single flat orthogonal textile sheet. Some examples include Cabral et al's dynamic light filters [16] and Knittel et al's self-folding knitted textiles [17].…”
Section: Programming Geometric Transformationsmentioning
confidence: 99%
“…This enables complex faceted or curved geometries from folding a single flat orthogonal textile sheet. Some examples include Cabral et al's dynamic light filters [16] and Knittel et al's self-folding knitted textiles [17].…”
Section: Programming Geometric Transformationsmentioning
confidence: 99%
“…Similarly, Huang et al suggested an integrated SMA wire into woven fabrics used as sleeves to shorten them upon heating up and elongating again when the environment becomes cooler [56], while SMA wires were integrated into knitted fabrics to enable new design aesthetics [57]. Special Origami techniques were used by Cabral et al to design dynamic light filters, based on SMA wires integrated in woven fabrics [58], and Liu et al applied Miuraorigami designs to prepare samples for compressive loading [59].…”
Section: Shape Memory Textiles With Integrated Shape Memory Alloy Wiresmentioning
confidence: 99%
“…[48] This property has allowed to develop t-shirts that do not need ironing, [49] clothes that can help to maintain the body temperature, [50] peristaltic devices, [51] or dynamic light filters. [52] SMAs also present behavior called superelasticity or pseudoelasticity. This property is observed when, without any temperature change, the alloy can return to its original shape after a mechanical strain has been applied and then is withdrawn.…”
Section: Order Changementioning
confidence: 99%